Eksplorasi pengalaman pengguna perpustakaan digital: perspektif pengaruh teknologi terhadap layanan - Nasrul Makdis; Lusi Ismail; Delvalina Delvalina; Deka Putri Naryanti (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2026)
Digital libraries have become a strategic component in supporting the transformation of higher education, including at UIN Imam Bonjol Padang. This study aims to explore user experiences in accessing and utilizing digital library services, particularly in the context of technology integration and user interaction. Using a qualitative exploratory approach, data were collected through in-depth interviews with 20 students from various academic programs. Thematic analysis was conducted to identify patterns of experience, perceptions, and challenges faced by users. The findings indicate that digital libraries provide ease of access, support for academic tasks, and enhance students' information literacy. However, several obstacles remain, such as limited digital collections, technical issues, and a lack of interactive guidance. These results highlight the importance of strengthening technological infrastructure, improving the quality of digital services, and fostering cross-sector collaboration to optimize the role of digital libraries in the digital transformation of higher education. This study offers both conceptual and practical contributions to the development of more responsive and user-centered library service strategies.